Performance Analysis of Slotted Optical Packet Switching Scheme in Non-Uniform Traffic Pattern Using Reservation Bit Technique - Kavitha, A.; Rajamani, V.; Kumar, P. Anandha (INFOCOMP Journal of Computer Science, 2009)
Improvement in the performance of optical networks in terms of Quality of Service is achieved using an optical packet switching technique. Slotted optical packet switching mechanism employed in non-uniform traffic pattern is analyzed by using a novel Reservation Bit technique. Minimum packet loss is achieved by employing buffers in contrast to the use of buffer-less slotted optical packet switching in non-uniform traffic pattern. Performance of Reservation Bit algorithm is analyzed for different Service classes and is compared with First-Fit wavelength assignment algorithm. Also, delay rate for different traffic pattern is found and analyzed.